New opportunities for collaboration between physicians and pharmacists in Poland in the context of implementing coordinated care and pharmaceutical care - Renata Bogusz (Polish Pharmaceutical Society, 2023)
The aim of the paper is to identify new opportunities for cooperation between doctors and pharmacists in Poland in the situation of implementing coordinated care and pharmaceutical care. In the first part of the article, the effectiveness of the interprofessional therapeutic team's action in caring for the health and life of patients was emphasized, and the necessity of changing the previously dominant model of the relationship between doctors and pharmacists was justified. The argumentation focused on the characteristics and potential perspectives for improving the health condition of society, staffing resources, and the specificity of the current functioning of the healthcare system, as well as the consequences of limited possibilities to secure health needs during the SARS-CoV-2 pandemic. It was assumed that the process of implementing coordinated care in the primary healthcare sector and pharmaceutical care would allow the potential of pharmacists to be adequately utilized and enable the expansion and integration of existing forms of cooperation between doctors and pharmacists. In the main part of the work, a brief characterization of coordinated care was made, stating that pharmacists should be involved in its implementation at every level of actions taken, for all groups of patients under care, and in the situation of therapy of each of the disease entities, legally indicated for the coordination of medical actions. Subsequently, elements of pharmaceutical care (pharmaceutical consultations, medication review, issuing prescriptions as part of the continuation of a medical order, diagnostic tests, pharmaceutical care plan) were presented, in the implementation of which the pharmacist, legally defined as an independent medical worker, has gained new possibilities for supporting the patient and the attending physician. In conclusion, it was stated that including a pharmacist providing pharmaceutical care in the process of coordinated care for a patient, in many situations, may constitute real and very significant help for the doctor, bringing considerable benefits in improving patient health outcomes, especially in the elderly or those treated for chronic diseases.